Sensory Processing and Integration at the Carotid Body Tripartite Synapse: Neurotransmitter Functions and Effects of Chronic Hypoxia - Leonard, Erin M.; Salman, Shaima; Nurse, Colin A. (Frontiers in Physiology, 2018)
Maintenance of homeostasis in the respiratory and cardiovascular systems depends on reflexes that are initiated at specialized peripheral chemoreceptors that sense changes in the chemical composition of arterial blood. In mammals, the bilaterally-paired carotid bodies (CBs) are the main peripheral chemoreceptor organs that are richly vascularized and are strategically located at the carotid bifurcation. The CBs contribute to the maintenance of O2, CO2/H+, and glucose homeostasis and have attracted much clinical interest because hyperactivity in these organs is associated with several pathophysiological conditions including sleep apnea, obstructive lung disease, heart failure, hypertension, and diabetes. In response to a decrease in O2 availability (hypoxia) and elevated CO2/H+ (acid hypercapnia), CB receptor type I (glomus) cells depolarize and release neurotransmitters that stimulate apposed chemoafferent nerve fibers. The central projections of those fibers in turn activate cardiorespiratory centers in the brainstem, leading to an increase in ventilation and sympathetic drive that helps restore blood PO2 and protect vital organs, e.g. the brain. Significant progress has been made in understanding how neurochemicals released from type I cells such as ATP, adenosine, dopamine, 5-HT, ACh, and angiotensin II help shape the CB afferent discharge during both normal and pathophysiological conditions. However, type I cells typically occur in clusters and in addition to their sensory innervation are ensheathed by the processes of neighboring glial-like, sustentacular type II cells. This morphological arrangement is reminiscent of a ‘tripartite synapse’ and emerging evidence suggests that paracrine stimulation of type II cells by a variety of CB neurochemicals may trigger the release of ‘gliotransmitters’ such as ATP via pannexin-1 channels. Further, recent data suggest novel mechanisms by which dopamine, acting via D2 receptors, may inhibit action potential firing at petrosal nerve endings. This review will update current ideas concerning the presynaptic and postsynaptic mechanisms that underlie chemosensory processing in the CB. Paracrine signaling pathways will be highlighted, and particularly those that allow the glial-like type II cells to participate in the integrated sensory response during exposures to chemostimuli, including acute and chronic hypoxia.